Laparoscopic surgery for strangulated diaphragmatic hernia after radiofrequency ablation for hepatocellular carcinoma: a case report - Yasuaki Kimura; Daisuke Ishioka; Hidenori Kamiyama; Shingo Tsujinaka; Toshiki Rikiyama (Surgical Case Reports)
Abstract Background Percutaneous radiofrequency ablation (RFA) is an effective treatment for hepatocellular carcinoma (HCC), but delayed thermal damage can cause diaphragmatic hernia (DH). Surgery is recommended for DH, and open surgery is widely accepted. This report presents a case of laparoscopic surgery for strangulated DH that occurred after RFA. Case presentation An 80-year-old woman with a history of hepatitis C-induced liver cirrhosis and HCC was admitted to our institution owing to sudden-onset intense epigastric pain. Twenty-two months earlier, she received RFA treatment for HCC located in segment 6/7. Contrast-enhanced computed tomography revealed herniation of the small intestine into the thoracic cavity, with mesenteric fat haziness. Emergency laparoscopic surgery was performed, and the patient was diagnosed with strangulated DH associated with the prior RFA. The defect was closed using absorbable sutures, and the ischaemic small intestine was resected via mini-laparotomy. The patient was discharged on the 10th postoperative day without complications, and no evidence of DH recurrence 15 months after surgery was noted. Conclusions Laparoscopic surgery seems useful and feasible for strangulated DH.